Handbook of Industrial and Hazardous Wastes Treatment, Second Edition - Wang, Lawrence (CRC Press, 2009)
Presenting effective, practicable strategies modeled from ultramodern technologies and framed by the critical insights of 78 field experts, this vastly expanded Second Edition offers 32 chapters of industry- and waste-specific analyses and treatment methods for industrial and hazardous waste materials-from explosive wastes to landfill leachate to wastes produced by the pharmaceutical and food industries.